Curvature And Twist Monitoring Using Tapered Fiber Sensor - Oon, Wui Liam (2021)
Structural health monitoring (SHM) is a sensor technology for real-time monitoring and damage detection on civil infrastructure through monitoring parameter of the structural such as curvature, deflections, torsions, and strains. This project presents a study of optical fiber sensing system based on tapered fiber for curvature and twist monitoring which can apply on curvature monitoring of roof truss in building. The low fabrication cost and ease of fabrication advantages of tapered fiber make it popular among researchers, but the lack of mature multiplexing scheme for intensity modulated sensor has reduced the practical values of tapered fiber sensor. In this project, two different designs of taper based optical sensor were used in multiplexed curvature sensing and twist sensing. The purposes are to determine the feasibility of tapered fiber sensor in real field test, design a multiplexing sensing array for tapered fiber sensor and design a novel fiber sensor with built-in multiplexer using tapered fiber. In the first part of the project, two taper based in-line Mach-Zehnder Interferometer (MZI) optical sensors were subjected to curvature sensing on cold-formed steel (CFS) roof truss. Both sensors were attached to CFS roof trusses with the same dimensions of 0.481m x 2.891m x 0.2m with different structural designs. The trusses were subjected to different load tests to determine the performance of MZI sensor under different circumstances. In the first cyclic load test, the MZI sensor achieved ±5% of deviation compared to the commercial LVDT sensor in the repeatability test. Whereas in the failure load test, the MZI sensor is ±3% deviation from LVDT sensor and it was able to discriminate the bending direction change when the truss was loaded to failure.To improve the practical value of the study, a simple and direct sensing array was demonstrated to operate multiple MZI sensors simultaneously. A parallel topology consisting of two MZI sensors was attached to a hardened steel bar and subjected to curvature measurement. Both sensors shared the same optical source but different optical detectors at the output. A real time monitoring on both MZI sensors was demonstrated and achieved sensitivities of 25.095 dB/km and 29.1 dB/km respectively. The mapping of pristine to multiplexed sensor signal shows a regression coefficient, ? of 96.06%, which indicates that the multiplexing setup does not compromise on the sensitivity of the curvature sensor.In the second tapered sensor design, two loop-integrated tapered fiber (LITF) sensors were fabricated and subjected to multiplexed twist measurement. The LITF sensors have the capability to conduct twist sensing and sub-carrier multiplexing simultaneously through the micro-bending sensitive taper. When subjected to torsion, the output optical power changes linearly with the twist angle. The power modulated signals from both sensors were modulated with a 300 Hz and 250 Hz sub-carrier frequency respectively using acoustic source to discriminate the signals through an overlapping spectrum. Both LITF sensors achieved sensitivities of 0.1634 dB/0 and 0.1457 dB/0 respectively in the twist measurement. The multiplexing sensing of two LITF sensors using sub-carrier multiplexing (SCM) was demonstrated. To determine the influence of the SCM system to the sensing, a comparison study between pristine and multiplexed setup was conducted. Extinction ratio of the pristine signal is 31.7 dB and multiplexed signal is 25.9 dB, where the attenuation of signal due to SCM system is less than 20%.